Advance Pricing Agreements in India: A Revolution in Taxation Law - Verma, Avani; Singh, Surabhi (Christ University Law Journal, 2021)
Double taxation is one of the biggest challenges faced by multinational corporations, especially when the taxable transaction is between associated enterprises. The determination of transfer pricing becomes a bone of contention among the revenue authorities of different countries. One mechanism to counter this problem is to take recourse to „Advance Pricing Agreement‟ (APA). An APA is an arrangement entered into between revenue authority(s) and the taxpayer to determine the transfer pricing in advance. It has a plethora of advantages and procedural benefits over the conventional methods of determination of transfer pricing. APA, which was in existence in many countries for many years, was recently introduced in India. The aim of this paper is primarily to explore the Indian law on APA in the light of the situation prevalent in other countries, and to suggest measures to improve the same. This aim shall be achieved by firstly studying the concepts pertaining to transfer pricing and the problems associated with it, which has led to the emergence of APA. Thereafter, an overview of the Indian APA regime is provided. Further, in order to evaluate the merits and demerits of Indian APA, a comparative study with the law on APA in other countries has been presented, while simultaneously making certain suggestions to make the Indian APA system robust. In the last part of the paper, some suggestions apart from those which were made after analyzing the comparative law have been made. If India improves upon its APA regime by taking a cue from other countries, and by implementing measures such as the creation of safe harbours, better dispute settlement mechanism, easier documentation etc., then the APA will surely bring the much desired revolution in the taxation of multinational corporations.